2016
DOI: 10.1002/chem.201505035
|View full text |Cite
|
Sign up to set email alerts
|

Confined‐Volume Effect on the Thermal Properties of Encapsulated Phase Change Materials for Thermal Energy Storage

Abstract: We have encapsulated the heat exchange material, n-docosane, into polyurethane capsules of different sizes. Decreasing the size of the capsules leads to changes of the crystallinity of phase-change material as well as melting/crystallization temperature. The novelty of the paper includes 1) protection of the nanostructured energy-enriched materials against environment during storage and controlled release of the encapsulated energy on demand and 2) study of the structure and surface-to-volume properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…The data reported in Table 3 show that the peak melting temperature (Tm) measured on the microcapsules is lower than that of the neat docosane, and this is more evident for the smaller (MC1) than for the bigger (MC2) capsules. This effect, also reported by other literature studies [29,30,31,33,59,60,61], can be ascribed to the fact that the confinement in a small volume hinders the crystallization, but in this specific case also to the interaction of docosane with the inner shell surface, which limits the chain mobility as evidenced by NMR studies (see Section 3.1.5). This hypothesis is supported by the reduction in the melting enthalpy, which is more evident for the smaller capsules presenting a higher surface-to-volume ratio.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The data reported in Table 3 show that the peak melting temperature (Tm) measured on the microcapsules is lower than that of the neat docosane, and this is more evident for the smaller (MC1) than for the bigger (MC2) capsules. This effect, also reported by other literature studies [29,30,31,33,59,60,61], can be ascribed to the fact that the confinement in a small volume hinders the crystallization, but in this specific case also to the interaction of docosane with the inner shell surface, which limits the chain mobility as evidenced by NMR studies (see Section 3.1.5). This hypothesis is supported by the reduction in the melting enthalpy, which is more evident for the smaller capsules presenting a higher surface-to-volume ratio.…”
Section: Resultssupporting
confidence: 73%
“…Although these studies evidence the potentialities of sol–gel encapsulation and consider a quite broad range of PCMs, to the best of the author’s knowledge, only one study has been reported on the production of organosilica microcapsules with docosane as the PCM [27], which specifically refers to the encapsulation of n-docosane in ZnO/SiO 2 shells prepared from TEOS. Docosane features a high phase change enthalpy and a melting/crystallization temperature of 41/33 °C, which makes it suitable for a wide range of applications, including thermal regulating fabrics, passive cooling systems for electronic devices, solar space heating materials and other solar thermal energy applications [32,33,34]. Moreover, although the reported research investigates the microstructural properties of the microcapsules to some extent, no studies have been found that use powerful techniques, such as the nuclear magnetic resonance (NMR), to deeply examine the phase change behavior in a confined volume, and relate the results to the outcome of microstructural and thermal analyses, such as X-ray diffraction (XRD) and differential scanning calorimetry (DSC).…”
Section: Introductionmentioning
confidence: 99%
“…Felix et al have fabricated docosane loaded capsules using polyurethane as shell material, controlling size by varying homogenisation speed. 9 , 130 The capsules were stable over at least 100 heat uptake/release cycles. An interesting effect was that the smaller capsules displayed higher latent heat compared with larger capsules.…”
Section: Encapsulation Of Organic Pcmsmentioning
confidence: 99%
“…SHS is the simplest and most developed form of heat storage, however, it suffers from low energy density and loss of thermal energy at any temperature. 9 …”
Section: Introductionmentioning
confidence: 99%
“…The sizes of PCM microcapsules are crucial to their thermal storage performance, especially for MPCM slurry application 160,[223][224] . The particle size distribution (PSD) of microcapsules can be measured using a diameter distribution analyzer 107 or a scanning electron microscope (SEM) 90, .…”
Section: Microcapsule Size Distributionmentioning
confidence: 99%